Pahangine A and B, two new oxetane containing neolignans from the barks of Beilschmiedia glabra Kosterm (Lauraceae) - Sulaiman, Syazreen Nadia; Zahari, Azeana; Liew, Sook Yee; Litaudon, Marc; Issam, A.M.; Wahab, Habibah A.; Awang, Khalijah (Elsevier, 2018)
Phytochemical investigation on the barks of Beilschmiedia glabra Kosterm led to the isolation of two new oxetane containing neolignans, Pahangine A (1) and Pahangine B (2) together with eight known compounds. The structures of isolated compounds were elucidated by extensive spectroscopic analysis including 1D and 2D NMR (1H–1H COSY, HSQC, and HMBC), DEPT-Q NMR, and by comparing with the published data. A possible biosynthetic pathway for the formation of 1 and 2 was proposed.